SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BEASISWA PADA SMK AL BASYARIAH DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Sonil Hermawan; Taufik Baidawi (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
Acceptance of scholarships is still a lot of problems that often occur for example inaccurate selection process because many students who want to get scholarships according to existing criteria Process that is still manual is also an obstacle in determining scholarship recipients because student data will be compared one by one and it takes enough the old time must first require accuracy. Al Basyariah School Vocational School in the Citayam area provides scholarships to outstanding students or underprivileged students, the number of scholarships is limited in a certain amount. The method used in determining the eligibility of scholarships for outstanding students is Simple Additive Weighting (SAW). The purpose of this study is to determine students who meet the requirements and criteria to get scholarship appropriately. The results of calculations using the Simple Aditive Weighting method by referring to the criteria for the average value, attendance, and income of parents, then selected three students who will get a scholarship, namely Nurhezha Salmased, Sindy Marlianti, Anita Sania Zahra.